Journal Geon Vol 4 No 2 July December 2017 (GEON Journal (Management, Organizations and Business), 2017)
Journal Geon Vol 4 No 2 July December 2017 Complete Journal
Keywords: human management; entrepreneurship; management; marketing; accounting; sustainable development; economy